Estimation of sedimentation and grain quality indicators of the winter bread wheat varieties - О. A. Nekrasova; N. S. Kravchenko; N. G. Ignatieva; M. M. Kopus; D. M. Marchenko (Зерновое хозяйство России)
The current paper has presented the study results of SDS-sedimentation and grain quality indicators of the winter bread wheat varieties in an interstation variety testing from the research institutions of the Russian Federation, Ukraine and France. The research work was carried out in 2017–2019 in the field of the laboratory for breeding winter bread wheat, the forecrop was maize for grain. The purpose of the research was to estimate SDS-sedimentation, protein percentage in grain, quantity and quality of gluten in the winter bread wheat varieties of interstation variety testing, for the subsequent introduction of the best samples in the breeding process aimed at improving grain quality. Grain quality indicators of the winter bread wheat varieties were identified in the laboratory for biochemical estimation of breeding material and grain quality using IR spectroscopy on ‘SpektraStar 2200’ analyzer. There was established that according to the SDS-sedimentation most of the samples corresponded to strong wheat (50–63 ml). There have been identified the genotypes with the highest values of this trait, such as ‘Shef’ (58 ml), ‘Nakhodka’ (59 ml) and ‘Don 107’ (61 ml). The largest gluten content in grain was identified in the varieties ‘Don 107’, ‘Shef’, ‘Kavalerka’, ‘Timiryazevka 150’ and ‘Nakhodka’ (25.5–26.2%). The largest protein percentage in grain has been identified in the varieties ‘Don 107’, ‘Shef’, ‘Aksinya’, ‘Nakhodka’ and ‘Timiryazevka 150’ (12.5-12.8%). The varieties ‘Don 107’, ‘Shef’, ‘Nakhodka’ and ‘Timiryazevka 150’ were identified according to the studied traits and were recommended to be involved in the breeding process as parental forms.